Psychological factors for an injury free athletic career - Tranaeus, U.; Hallgren, L.; Jörlund, H. (British Journal of Sports Medicine, 2021)
Background Many athletes remain uninjured during their careers. Little is known about if and which psychological factors that may contribute to protect from athletic injuries.